Relaciones sociales en el estudio de caso Las Señoras de Los Cuyes que se dedican a la agricultura como mecanismo para solventar la economía familiar - Flores Olivo, Verónica Alexandra (2016)
This project is an investigation that was born of the visit to the San Ramon community, proposing to show teamwork women who live in this area and which ones are organized in a group called "Ladies of the guinea pigs." For this work was made a qualitative and quantitative perspective, where interviews, surveys and a focus group were used as research tools. It was determined what kind of social relations are among women engaged with to the agriculture, animal farming and taking care of small animals that made these activities a mechanism to help the family economy. - Through the conceptualization and description of topics about relationships of women to understand the behavior among them, also on the social context that surrounds them and in addition to the roles that women and men several types of social relations strengthen the joint work in this sector and this helps them to keep the group and perform balanced activities, which means that the woman delivers significant contribution in the family economy of the community. The result of this research will be reflected in the writing of a scientific article to talk about "guinea pigs Ladies" and relationships between them and how this strengthened teamwork.